2012
DOI: 10.1136/bmjopen-2011-000666
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis among people with diabetes mellitus: an Australian nationwide cohort study

Abstract: ObjectivePrevious studies that have found an increased risk for tuberculosis (TB) in people with diabetes mellitus (DM) have been conducted in segments of the population and have not adjusted for important potential confounders. We sought to determine the RR for TB in the presence of DM in a national population with data on confounding factors in order to inform the decision-making process about latent tuberculosis infection (LTBI) screening in people with diabetes.DesignWhole population historical cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 18 publications
6
85
3
3
Order By: Relevance
“…Diabetes has also been associated with tuberculosis in several studies (5)(6)(7)(8) and has been shown to be a risk factor for severe gram-positive infections (9,10), hospital-acquired postoperative infections (11,12), and urinary tract infections (3).…”
mentioning
confidence: 99%
“…Diabetes has also been associated with tuberculosis in several studies (5)(6)(7)(8) and has been shown to be a risk factor for severe gram-positive infections (9,10), hospital-acquired postoperative infections (11,12), and urinary tract infections (3).…”
mentioning
confidence: 99%
“…U populacijama sa češćom pojavom tuberkuloze rizik za tuberkulozu je veći kod bolesnika sa dijabetesom koji su na insulinskoj terapiji naročito kod onih koji su na visokim dozama insulina. Za razliku od prethodnog, u populacijama sa niskom incidencom za tuberkulozu kao što je Australija, rizik za pojavu tuberkuloze kod bolesnika sa dijabetesom nije povećan [8]. Studije koje su se bavile učestalošću tuberkuloze u odnosu na pol, dale su oprečne rezultate [9], a u našoj studiji, iako je postojala razlika u odnosu muš-karaca i žena u dvije ispitivane grupe, ona nije bila statistički značajna.…”
Section: Diskusijaunclassified
“…In Zambia, another country with a very high TB burden (462/100,000 population), it was found that TB comorbidity was significantly associated with DM (OR = 6.5, 95% CI 1.7-25.3) 13,14 . Conversingly, in countries with a low TB burden such as Australia (5.8/100,000), TB risk in diabetic patients was increased only moderately (adjusted relative risk RR = 1.48, 95% CI 1.04-2.10) 15 . In a cohort study from Hong Kong, patients with well-controlled DM had lower risk for TB 16 .…”
Section: Epidemiologymentioning
confidence: 99%